(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Where it receives and graduates huge numbers of students annually in various specializations that represent the cornerstone of community development. The descriptive-analytical method was used, and some material and organizational indicators affecting the scientific productivity of faculty members were addressed. The research reached several conclusions drawn from the body of the study, along with some solutions and recommendations regarding them.